Introduction to Comparative Government and Politics - Bozonelos, Dino; Wendt, Julia; Lee, Charlotte (Open textbook library., 2022)
Introduction to Comparative Government and Politics, 1st edition, is an Open Education Resource Textbook that surveys contemporary comparative politics. The textbook is organized thematically and includes chapters that cover a wide range of topics in comparative politics: how and what comparativists study; methods in comparative politics; states and regimes; democracies and democratization; non-democracies and democratic backsliding, political identity, including culture, race and ethnicity, gender, nationalism, religion, and class; political economy; collective action and social movements; comparative public opinion; political violence; and globalization and fragmentation. Each chapter accompanied by a case study or a comparative study, one of the main methodological tools used in comparative politics. By contextualizing the concepts, we hope to help students learn the comparative method, which to this day remains one of the most important methodological tools for all researchers.